Commercial varieties of Kappaphycus and Eucheuma in Malaysia - Phang, Siew-Moi; Yeong, Hui-Yin; Lim, Phaik-Eem; Md Nor, Adibi Rahiman; Tee Gan, Kian (Malaysian Journal of Science, 2010)
The seaweed industry has been identified for priority development in Malaysia. The seaweeds commercially farmed for carrageenan belong to the genera Kappaphycus Doty and Eucheuma J. Agardh. At least six varieties of Kappaphycus and Eucheuma are found in the farms around Sabah, east Malaysia. These seaweeds produce carrageenan with gel strength ranging from 250 to 550 g.cm-2. This paper provides a simple description of gross morphological features and illustrations that may be used in the field for differentiating the main seaweed varieties cultivated in Sabah.